Diseño de la red de internet de las cosas (iot) para el laboratorio de redes de la Carrera de Sistemas de Información de la Universidad Técnica de Cotopaxi - Guanochanga Quinaucho, Luis Fernando (2022)
Years ago, the internet of things was a very ambiguous concept for the common people, because it was a technology that was being tested and only a few companies made use of these devices because they were relatively expensive and did not show reliability when implementing them within these entities. Over the years they have been evolving and taking different forms in order to adapt to user requests, paying attention to factors such as better security, reliability, cost, accessibility and ease of use, to the point that these devices emerged in such an immense way that, although it may seem crazy, they exceeded the number of the world's population; Part of this success is due to the computation and programming that occupies each of these mechanisms allowing it to cover a wide range of possibilities in which it interacts automatically through monitoring both in the web section and in the applications developed for mobile devices where it will be stored both in the cloud on servers that offer such services; Therefore though this research project aims to make a proposal for the design of the Internet of Things (IoT) network for the network laboratory of the information systems career of the Technical University of Cotopaxi, in which a need for improvement in various aspects such as security, reliability, and simplification of processes that can offer this type of technology's estimated through the collection of bibliographic sources, interviews, and surveys; For this research the ISO/IEC 30141 standard was used the Top-Down methodology was applied for the design of networks developed in the 4 phases consisting of the application of the IoT simulation of the proposed network, both physical and logical, the testing and optimization of the network and the incorporation of the prototype.